136k views
3 votes
PLEASE HELP ASAP 25 POINTS

PLEASE HELP ASAP 25 POINTS-example-1

2 Answers

2 votes
therefore from the pictures attached to this answer (x, y)=(-3, 1)
PLEASE HELP ASAP 25 POINTS-example-1
PLEASE HELP ASAP 25 POINTS-example-2
User Mohit Ajwani
by
5.6k points
5 votes

Given Equations :

❤ -x + y = 4 --------------- [1]

❤ 3x - 4y = -13 -------------- [2]

Now Consider Equation [1]

⇒ -x + y = 4

⇒ y = x + 4

Substitute y = x + 4 in Equation [2]

⇒ 3x - 4(x + 4) = - 13

⇒ 3x - 4x - 16 = -13

⇒ -x = 16 - 13

⇒ x = -3

Substituting x = -3 in Equation [1], We get :

⇒ 3 + y = 4

⇒ y = 1

⇒ (x , y) = (-3 , 1)

Option (b) is the Answer

User Aamir Rind
by
6.4k points